1970
DOI: 10.1136/bmj.4.5729.214
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Menorrhagia with Tranexamic Acid. A Double-blind Trial

Abstract: ummary: In a double-blind trial tranexamic acid (Cyclokapron) 1 g. four times a day for the first four days of menstruation, significantly decreased menstrual blood loss in women with menorrhagia for which no organic cause had been found. No difference in side-effects was noted between the active and placebo treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(51 citation statements)
references
References 7 publications
1
49
0
Order By: Relevance
“…Treatment with tranexamic acid was found to reduce MBL by 34-54% compared to a placebo in different studies [21,22,23]. Our results (60.8% decrease in blood loss) were slightly more successful and were similar to the results of a phase 3, open prospective trial by Gultekin et al [24], who reported a 65.9% success rate in 2009.…”
Section: Discussionsupporting
confidence: 80%
“…Treatment with tranexamic acid was found to reduce MBL by 34-54% compared to a placebo in different studies [21,22,23]. Our results (60.8% decrease in blood loss) were slightly more successful and were similar to the results of a phase 3, open prospective trial by Gultekin et al [24], who reported a 65.9% success rate in 2009.…”
Section: Discussionsupporting
confidence: 80%
“…The demonstration of high levels of endometrial fibrinolytic activity in women with menorrhagia provides a rationale for their use in this setting [62,63]. Several studies reported that tranexamic acid reduced objectively confirmed menstrual blood loss by 34-59% compared to baseline or placebo in women with idiopathic menorrhagia not due to bleeding disorders [47,[64][65][66][67]. A recent meta-analysis found a similar 47% reduction in mean menstrual blood loss [68].…”
Section: Antifibrinolytic Therapymentioning
confidence: 99%
“…Several studies of variable design have been carried out to assess the therapeutic efficacy of tranexamic acid in the treatment of idiopathic menorrhagia [166][167][168][169][170]. Using oral tranexamic acid ranging from 500 mg or 1 g four times daily for 4-7 days per cycle, the menstrual blood loss was reduced by 34-59% over two to three cycles in women with menorrhagia.…”
Section: Medical Treatment Of Menorrhagiamentioning
confidence: 99%